Effectiveness of Using Misoprostol and Oxytocin in the Management of Post Partum Haemorrhage - Rayung Andadari Yoelandha; Tuty Yanuarti (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2023)
Aims: In 2020, the WHO estimated that as many as 295,000 women died during and after pregnancy and childbirth. Ninety percent of maternal deaths are caused by complications that arise during and after delivery, including hemorrhaging. Misoprostol, a prostaglandin analogue, is useful for treating postpartum hemorrhage for a number of reasons, including its efficiency, low cost, stability in heat, user-friendliness, and low risk of adverse effects. Oxytocin is a medication frequently used to induce labor. Methods : Quasi experimental with one group pretest-posttest design. The sample in this study were all 18 pregnant women who experienced postpartum hemorrhage at TPMB "I" in June-December 2022, the sampling technique was total sampling. Results : The average postpartum bleeding in laboring mothers before misoprostol and oxytocin was 406.39, and it was 141.67 afterward. Misoprostol and oxytocin are beneficial in reducing postpartum hemorrhage in TPMB "I" patients from June to December 2022 (p.value 0.000). Conclusions : There is an effectiveness of using misoprostol and oxytocin in postpartum hemorrhage. It is expected that midwives can provide services in normal delivery using misoprostol and oxytocin safely.